Cartografias do cuidado em saúde mental: o Piauí em cena - Lima, Emanoel José Batista de (2015)
The Psychiatric Reform consists of a complex social process and it involves a polyvalent range of transformations in society regarding the mad and madness, it proposes and struggles for epistemological, juridical-political, social-cultural and technical-assistance changes. The health care field has striven to be one of the main makers of such changes. The Brazilian mental healthcare policy provided by SUS has been grounded in reformist propositions and has implemented substitute services instead of psychiatric hospitals as of the early 1990 s, most specifically the Centers for Psychosocial Assistance (CAPS). New practices must guide the new service actions, breaking the traditional activities of asylum character. The present thesis aims to map, according to professional practices on mental care, the ways of subjectivation incorporated in a CAPS of Piauí State. The mapping method inspired the work according to ethnographic experiments applied throughout 04 months together with the making of a field diary. The situations and reports experienced daily at the service were analyzed according to Michel Foucault s categories/thought lines concerning ways of subjectivation and care of oneself. We also assessed the mental health care policy context in Piauí in a historic perspective (chapter 1), as well as systemized the uses and meanings of care in psychosocial assistance. In general terms, two major lines were mapped: 1 ways of subjectivation connected to traditional practices towards the mad and based on relations of power that promote sujbjetions (they have been extremely present throughout the mapping course); 2 process of subjectivation produced from mental health care practices based on psychosocial assistance and that produce variation effects in relation to dominant ways of subjectivation. Despite the maintenance of traditional practices, characterized by medicalization, tutelage, segmentation, stigmas, among others, innovative forms of care have been drawn in order to enable new ways of life, in a movement that has the potency to contribute to the creation of new subjects, new forms of sociability and, hence, a new society. Increasing this new care frequency/consistency also depends on how professionals approach their fieldwork, mainly in the meetings with patients and their singular was of dealing with life